STUDY ON EFFICACY OF GUNJA TAILA SHIRO ABHYANGA AND NIMBA TWAK CHURNA IN THE MANAGEMENT OF DARUNAKA W.S.R TO PITYRIASIS CAPITITIS - Krishna Naik, *D.Venkata; Babu, P.Srikanth (International Journal of Ayurveda and Pharma Research, 2017)
Back ground: In Ayurveda head is said to be root of the plant for possessing all special senses and Prana, so one has to protect and care the head. In modern era, among diseases related to head due to varying factors lot of people suffering from this faulty lifestyle related disorders, in this context visual perception of individually distinguishable flakes on the scalp, in the hairs, or on the clothing is considered an abnormal condition frequently referred to as Pityriasis capititis i.e., Dandruff (Darunaka). Darunaka is an irritative disease of the scalp, affecting almost half of the population at the pre-pubertal age and of any gender and ethnicity. It occurs in both sexes and persons of all races. The response to treatment is commonly swift, but transient..So there is a need to find a safe and effective remedy in the management of Darunaka, which initiated for the study. Aims of study: To evaluate the efficacy of Gunjatailashiroabhyanga and Nimbatwak churna in the management of Darunaka i.e Pityriasis Capititis. Materials and Methods: It was an open trail randomised clinical study of 30 patients, was taken for the study with pre and post-test design. The patients were assigned to single group and were administered Gunjataila and Nimbatwak Churna for a duration of 40 days and the results were analysed statistically. Results: Results were assessed in terms of change in subjective parameters taken before and after the treatment. Out of 30 pts,8pts got Complete relief,15ptsgot good relief, and 7 pts got moderate relief. Conclusion: The present study reveals that clinically Gunjatailashiroabhyanga with Nimbatwak churna showed better results in treating Darunaka.